Gamification in Enhancing Student Financial Knowledge, Engagement, and Enjoyment in Financial Education - Yulianto, Arief; Pramono, Suwito Eko; Wijaya, Angga Pandu; Nasrun, Nasrun (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to examine the impact of gamification on financial knowledge through student enjoyment and student engagement. This study employed a quantitative approach and used a survey to examine the relationships between variables. The sampling technique used was purposive sampling, with 289 students who have previously received financial education at a public university participating as respondents. The research instrument utilized a questionnaire developed based on prior studies. The results were tested using Variational Bayesian Structural Equation Modeling (VB-SEM) to analyze the influence between variables. The findings showed that gamification had a positive impact on student enjoyment and student engagement. This study demonstrates that gamification does not directly influence students' financial knowledge. Student engagement fully mediated the effect of gamification on students' financial knowledge, whereas enjoyment does not affect students' financial knowledge. This study underscores the importance of fostering student engagement in gamification to enhance financial knowledge. The implications of this research include strengthening student engagement through various strategies, such as apperception, motivation, and interaction during the use of gamification in financial education.